The Pengaruh Product, Place, Dan Price Terhadap Kepuasan Konsumen (Studi Pada Perumahan Grand Taruma Pengembang Agung Podomoro Group) - Julitas Silaban; Solehudin Solehudin; Edi Suwadji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The research conducted by the author aims to determine the large or small influence of product, place, and price on consumer satisfaction. The author conducted research at the GT Karawang Housing. Meanwhile, in this study, it is influenced by Product (x1), Place (X2) and Price (X3) on consumer satisfaction, namely (y). In this research method, the writer covers the types of research, namely data sources, population, data processing techniques and data analysis. In this study also included by conducting interviews and field research as data collection techniques and analysis using simple regression analysis. The respondents used by the author are 120 residents in Grand Taruma Karawang using Spss. And the results in this study have an effect on x1, x2, x3 which have a significant positive effect on y. as for the effect of x1 that is 0.726 to y. the effect of x2 on y is 0.251 on y and x3 on y is 0.189. based on the data analysis and hypothesis testing, in this case it shows that there is a strong influence between x1, x2, x3 on y. with the linear equation y=0.726x1+0.251x2+0.189x3. Keywords: Product, Place, Price and Consumer Satisfaction